Studies on spinel cobaltites, MCo2O4 (M = Mn, Zn, Fe, Ni and Co) and their functional properties. Issue 5 (1st April 2018) - Darbar, Devendrasinh; Anilkumar, M.R.; Rajagopalan, Vijayaraghavan; Bhattacharya, Indranil; Elim, Hendry Izaac; Ramakrishnappa, T.; Ezema, F.I.; Jose, Rajan; Reddy, M.V.
Abstract: Optimization of electrodes for charge storage with appropriate processing conditions places significant challenges in the developments for high performance charge storage devices. In this article, metal cobaltite spinels of formula MCo2 O4 (where M = Mn, Zn, Fe, Ni and Co) are synthesized by oxalate decomposition method followed by calcination at three typical temperatures, viz. 350, 550, and 750 °C and examined their performance variation when used as anodes in lithium ion batteries. Phase and structure of the materials are studied by powder x-ray diffraction (XRD) technique. Single phase MnCo2O4, ZnCo2O4 and Co3O4 are obtained for all different temperatures 350 °C, 550 °C and 750 °C; whereas FeCo2 O4 and NiCo2 O4 contained their constituent binary phases even after repeated calcination. Morphologies of the materials are studied via scanning electron microscopy (SEM): needle-shaped particles of MnCo2 O4 and ZnCo2 O4, submicron sized particles of FeCo2 O4 and agglomerated submicron particle of NiCo2 O4 are observed. Galvanostatic cycling has been conducted in the voltage range 0.005–3.0 V vs. Li at a current density of 60 mA g −1 up to 50 cycles to study their Li storage capabilities. Highest observed charge capacities are: MnCo2 O4 – 365 mA h g −1 (750 °C); ZnCo2 O4 – 516 mA h g −1 (550 °C); FeCo2 O4 – 480 mA h g −1 (550 °C); NiCo2 O4 – 384 mA h g −1 (750 °C); and Co3 O4 – 675 mA h g −1 (350 °C). The Co3 O4 showed the highest reversible capacity of 675 mA h g −1 ; the NiO present in NiCo2 O4 acts as a buffer layer that results in improved cycling stability; the ZnCo2 O4 with long needle-like shows good cycling stability. Graphical abstract: fx1